“Prevention of Death Anxiety by Familiarity with the Concept of Death” - Asadzandi Minoo (Journal of Preventive Medicine And Care, 2019)
Objectives Death is the only definitive phenomenon in life, and everyone is sure that it will happen in the future. Based on the philosophical perspective, the concept of death differs in different cultures. The purpose of this study was “explaining the difference between the concept of death from the perspective of theology and empirical science”. Methods In this qualitative evolutionary study, a targeted review was conducted to answer the question “what is the difference between the concept of death from the perspective of theology and empirical science?” Articles published between 1990 and 2018 were extracted from the PubMed, science direct, google scholar, SID, and Cochrane databases. At the same time, Islamic religious evidence (Quran and Hadiths) was investigated for understanding the concept of the death in Islam. The “Shia Seminary” research methodology was used to avoid interpretations of the Quran verses and to ensure the authenticity of the Hadiths. Findings Empirical sciences consider death as a biological phenomenon, which results from irreversible damage to cerebral hemispheres and brain stem (brain death) that causes grief process, fear, anxiety, and sadness. From the perspective of Islam, death is an existential phenomenon, the transfer of the soul from one world to another. Death is the complete reception of the soul from the body by the angels and the beginning of another life, in the
Keywords: death